ENRICHING STUDENTS’ SPEAKING ABILITY THROUGH FOCUS GROUP DISCUSSION TECHNIQUE - Magfirah, Nadila Ayu; Salija, Kisman; Korompot, Chairil Anwar (Universitas Negeri Makassar, 2022)
This research aimed to investigate whether focus group discussion enriches students’ speaking abilities. This research was conducted using pre-experimental research, with 40 students in the eleventh grade (second grade of senior high school) participating in this research. The result of this research was obtained from two tests (pre-test and post-test). The pre-test revealed that there were 36 students classified as very poor and 4 students classified as fair. The post-test showed that only 15 students were classified as very poor, 12 were classified as poor, 6 were classified as fair, 3 were classified as fairly good, and 4 were classified as good. In addition, the mean score from the pre-test (24.90) to the post-test (51.40) improved. The findings of this study showed that focus group discussions could enrich students’ speaking abilities. Therefore, the focus group discussion technique, which has been widely used in the world of work and organizations, has also proven to be a good method of teaching English, especially speaking.